Zasady dostępu do informacji publicznej oraz stosunek ustawy o dostępie do informacji publicznej do innych ustaw - Kamińska, Irena (Kwartalnik Prawa Publicznego, 2012)
This article discusses the rules concerning access to public information laid down in the Act of 6 September 2001 on access to public information. It also highlights the differences between this Act and specific legislation: the Act on protection of non-public information and the Act on the principles of development policy. The provisions of the specific acts often significantly narrow the circle of persons entitled to access particular information which is divergent from Article 2 of the Act on access to public information, stipulating that such information be accessible to all, with the reservation of Article 5 of this Act. Moreover, the Article presents issues observed in judicial practice which were a result of the different modes of access to public information.